Localization of Urokinase‐type Plasminogen Activator, Plasminogen Activator Inhibitor‐1, 2 and Plasminogen in Colon Cancer - Naitoh, Hiroyuki (Jpn J Cancer Res, 1995)
We examined the localization of urokinase‐type plasminogen activator (u‐PA), plasminogen activator inhibitors (PAI‐1 and PAI‐2) and plasminogen (plg) in 26 cases of colon cancer by immunohistochemical staining. The u‐PA antigen was detected in the cytoplasm of cancer cells (18/26) and stromal cells adjacent to cancer tissues (9/26). The localization of u‐PA mRNA examined by in situ hybridization was consistent with that of u‐PA antigen. The PAI‐1 antigen was detected in fibroblasts and endothelial cells (22/26), while PAI‐2 antigen was found in cancer cells (20/26). The plg antigen was seen in the extracellular matrix of the cancer stroma. The u‐PA expression in cancer cells was significantly more frequently detected in cases with lymph node metastasis than in cases without metastasis. In either PAI‐1‐ or PAI‐2‐expressing cases, lymph node metastasis seemed to be restrained. These findings indicate that cancer cells themselves produce u‐PA, and suggest that u‐PA converts plg into plasmin, which dissolves the extracellular matrix surrounding cancer cells, resulting in cancer invasion and metastasis. PAI‐1 and PAI‐2 may have inhibitory actions on cancer invasion and metastasis mediated by u‐PA.